SIMULASI RESPON PONDASI TIANG PANCANG AKIBAT PEMBEBANAN LATERAL MENGGUNAKAN METODE BEDA HINGGA - Sujatmiko, Ahmad Fitri (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
Structural response of concrete of pillar commonly happened from the result of in site testthrough loading test. But, the test needs large amount. So, it is suggested to use an efficient analysismethod through simulation of numeric model. A model of pillar on the homogeny land will be loadedby a horizontal weight. By considering strengthen of the pillar and the reaction of the ground, tosolve the accountability can be done by using finite differences method. For example, for a concreteof pillar 30x30cm with a lateral weight 1000kg are have lendutan response ymaks=42mm, while themaximum moment response Mmaks=780kg.mKeyword: concrete response, lateral weight, finite differences method.